ADIPOKINES AS MODIFIABLE RISK FACTORS OF CARDIOVASCULAR DISEASE - N. G. Veselovskaya; G. A. Chumakova; A. A. Kozarenko; M. I. Boxler (Российский кардиологический журнал, 2010)
Worldwide, obesity prevalence is reaching the level of epidemics. It has been demonstrated that the risk of cardiovascular disease development and progression is very high in obese patients. The main mechanism, underlying negative effects of adipose tissue on cardiovascular system, is its hormonal activity. Leptin, a hormone produced by white adipocytes, plays an important part in endothelial dysfunction, thrombogenesis, and atherogenesis. In obesity, the concentration of adiponectin, which has anti-atherogenic, anti-inflammatory, and insulin-sensitizing effects, is substantially decreased. Correction of such modifiable risk factors as hyperleptinemia and hypoadiponectinemia is one of the methods for cardiovascular prevention.